2018
DOI: 10.1002/jcb.26689
|View full text |Cite
|
Sign up to set email alerts
|

Localization of palmitoylated and activated G protein α‐subunit in Dictyostelium discoideum

Abstract: Guanine nucleotide-binding proteins (G proteins) act as molecular switches to regulate many fundamental cellular processes. The lipid modification, palmitoylation, can be considered as a key factor for proper G protein function and plasma membrane localization. In Dictyostelium discoidum, Gα2 is essential for the chemotactic response to cAMP in their developmental life cycle. However, the regulation of Gα2 with respect to palmitoylation, activation and Gβγ association is less clear. In this study, Gα2 is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…and therefore participates in modulating diversified cellular and physiological functions. [3][4][5] Previously, it was reported that Sept8-204, a transcript of Sept8 that is exclusively expressed in neuron, is modified by palmitoylation both in vitro and in vivo, 6,7 yet, many aspects of Sept8-204 palmitoylation at molecular and cellular levels remain largely unknown and invite further investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and therefore participates in modulating diversified cellular and physiological functions. [3][4][5] Previously, it was reported that Sept8-204, a transcript of Sept8 that is exclusively expressed in neuron, is modified by palmitoylation both in vitro and in vivo, 6,7 yet, many aspects of Sept8-204 palmitoylation at molecular and cellular levels remain largely unknown and invite further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…In general, dynamic protein palmitoylation may be involved in regulating protein subcellular localization, protein‐protein interaction, and signaling transduction and so forth. and therefore participates in modulating diversified cellular and physiological functions 3–5 . Previously, it was reported that Sept8‐204, a transcript of Sept8 that is exclusively expressed in neuron, is modified by palmitoylation both in vitro and in vivo, 6,7 yet, many aspects of Sept8‐204 palmitoylation at molecular and cellular levels remain largely unknown and invite further investigations.…”
Section: Introductionmentioning
confidence: 99%